Analysis of Outcomes of Laparoscopic Techniques for Inguinal Hernia Repair: A Cerrahpaşa Experience - Özkaya, Güney; Kutluk, Fadime; Akıncı, Ozan; Özçelik, Mehmet Faik (Cerrahpaşa Medical Journal, 2023)
Objective: The aim of this study is to compare the early and late postoperative outcomes of total abdominal preperitoneal and total extraperitoneal techniques. Methods: A retrospective analysis was made of 148 patients who underwent total extraperitoneal (n = 99) and total abdominal preperitoneal (n = 49) inguinal hernia repair between July 2016 and July 2019. The demographic characteristics of the patients, length of hospital stay, intraoperative and postoperative complications, postoperative chronic pain, and recurrence were examined. Results: The study sample consisted of 136 male (91.9%) and 12 female (8.1%) patients, with a mean age of 51.6 ± 14.9 years. Of the patients, 89.8% had primary and 71.6% had unilateral inguinal hernia. The mean follow-up was 19.2 (12–30) months. The rates of intraoperative and postoperative complications were similar in the groups (P > .05). The length of hospital stay was significantly longer in the total abdominal preperitoneal group (1.5 ± 1.04 days) than in the total extraperitoneal group (1.16 ± 0.53 days) (P = .024). The rate of postoperative chronic pain was 8.1% (n = 4) in the total abdominal preperitoneal group and 7.07% (n = 7) in the total extraperitoneal group (P = .811). Recurrence developed in 2 patients in the total extraperitoneal group and in 1 patient in the total abdominal preperitoneal group (P = .706). Conclusion: Both total abdominal preperitoneal and total extraperitoneal techniques are safe for inguinal hernia repair. The hospital stay was shorter in the total extraperitoneal group. There was no significant difference in intraoperative postoperative complications, intraoperative conversion to another technique, postoperative chronic pain, and recurrence between the 2 techniques. Cite this article as: Özkaya G, Kutluk F, Akıncı O, Özçelik MF. Analysis of outcomes of laparoscopic techniques for inguinal hernia repair: A cerrahpaşa experience. Cerrahpaşa Med J. 2023;47(1):51-54.